Adoption of AIOps Technology in IT Service Operations in Corporate Enterprises Using the Technology-Organization-Environment (TOE) Model - Rony Cahyadi; Andreas Jodhinata (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Along with the rapid technological developments in the current digital era, more companies are integrating artificial intelligence (AI) technology into IT operations services. This technological development also leads to increasingly sophisticated technology being used and an increasing amount of data received, the complexity and risk that can impact IT services in companies. Artificial intelligence technology for IT operations services (AIOps) addresses this challenge by integrating AI features comprehensively into all solutions available in IT operations services. AIOps changes the approach to handling incidents from a reactive to a proactive one by identifying potential problems before they occur. The purpose of this study is to define the factors influencing the adoption of AIOps technology in IT services in companies and analyze its impact on productivity and service stability. The Technology-Organization-Environment (TOE) method is used in this study because it has been widely applied in various adoption studies of various IT innovations ranging from e-commerce, ERP, Cloud Computing to the most recent adoption of AIOps technology. The TOE research method can accommodate various indicators of technology adoption that are tested by considering internal (organizational), technological and external (external environment) aspects to provide a comprehensive picture of the readiness and level of technology adoption within the company.